2016
DOI: 10.5897/jptaf2015.0123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biofuel production on selected local Communities in Nigeria

Abstract: . Since there are reported activities in biofuel feedstock as well as bio-ethanol and biodiesel productions in some parts of Nigeria, the geographical zones were selected and the production sites defined. The communities around the production sites were sampled with a questionnaire to obtain perceptions of the effects. The perceptions were statistically analyzed to derive the effects for each zone and to check for significant (p<0.05) difference in the effects. Results showed varying effects of biofuel product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In oil palm plantations, female workers usually work as collectors of FFB that fall and clean the shipyards around oil palm trees. Increasing employment opportunities for women is also demonstrated by Balogun and Salami [53], who reviewed the impact of biofuel production for local communities in Nigeria. The results of empirical study on the two research sites, especially in Riau Province showed that only one social indicator for sustainability has been a very critical issue.…”
Section: Social Sustainability Statusmentioning
confidence: 93%
See 1 more Smart Citation
“…In oil palm plantations, female workers usually work as collectors of FFB that fall and clean the shipyards around oil palm trees. Increasing employment opportunities for women is also demonstrated by Balogun and Salami [53], who reviewed the impact of biofuel production for local communities in Nigeria. The results of empirical study on the two research sites, especially in Riau Province showed that only one social indicator for sustainability has been a very critical issue.…”
Section: Social Sustainability Statusmentioning
confidence: 93%
“…In oil palm plantations, female workers usually gather fallen FFBs and clear weeds around oil palms. This increase in employment opportunities in rural areas, including for women, is a positive aspect of oil palm estates in many regions in Indonesia and in other tropical regions [52,53].…”
Section: Social Sustainability Statusmentioning
confidence: 99%